2020
DOI: 10.3389/fpsyg.2020.01535
|View full text |Cite
|
Sign up to set email alerts
|

Complementing the Self-Determination Theory With the Need for Novelty: Motivation and Intention to Be Physically Active in Physical Education Students

Abstract: The theoretical framework of the self-determination theory establishes that the satisfaction of basic psychological needs and more self-determined motivational forms are related to positive behavioral consequences and, therefore, may increase the intention to be physically active in Physical Education students. In this sense, the need for novelty has been proposed as a psychological need by recent scientific evidence, so it is necessary to prove its possible contribution to the prediction of young people's beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 39 publications
4
25
0
6
Order By: Relevance
“…The correlations were significant in their entirety and positive, except for those related to the frustration of basic psychological needs, which showed a negative sign. These results are in line with previous studies where the factors composing PE class satisfaction, BNPs satisfaction, self-determined motivation, factors composing social cognition, behavioural intention, and following a Mediterranean diet were determined to be constructs positively related to each other because of their positive connotations [ 41 , 42 , 43 ] and studies that have demonstrated that BPNs thwarting is negatively related to all of them [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 92%
“…The correlations were significant in their entirety and positive, except for those related to the frustration of basic psychological needs, which showed a negative sign. These results are in line with previous studies where the factors composing PE class satisfaction, BNPs satisfaction, self-determined motivation, factors composing social cognition, behavioural intention, and following a Mediterranean diet were determined to be constructs positively related to each other because of their positive connotations [ 41 , 42 , 43 ] and studies that have demonstrated that BPNs thwarting is negatively related to all of them [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, performing new and challenging exercises could increase enjoyment and interest while enhancing acquisition of new skills every time a new exercise is introduced. Moreover, it has been recently hypothesized that the need for novelty, that is the need to experience something that stands out of the routine (González-Cutre et al, 2019 ), could be one of the Basic Psychological Needs (Bagheri and Milyavskaya, 2020 ; Fernández-Espínola et al, 2020 ). In this sense, creating programs satisfying the need for novelty, and stimulating interest and enjoyment at the same time, could also promote individuals' participation over time, through the introduction of new exercises in the PA routine, or the variation of familiar exercises (Sylvester et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, social exergaming could also satisfy a (fourth) basic need for novelty (Vansteenkiste et al, 2020). While offering new experiences had a positive indirect effect on the intention to be physically active via autonomous motivation in school-aged students (Fernández-Espínola et al, 2020), playing with other players can result in new experiences. However, novelty effects (a rapid decline from an initially high level of appeal or usage) might also lead to an overestimation of exergames' (long-term) effects.…”
Section: Nonphysical Effects Of Social Exergaming At Homementioning
confidence: 99%